2007
DOI: 10.1016/j.porgcoat.2006.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and recovery of adhesion properties of deformed metal–polymer interfaces studied by laser induced delamination

Abstract: Degradation and recovery of adhesion properties of deformed metal-polymer interfaces studied by laser induced delamination Fedorov, A. V.; van Tijum, R.; Vellinga, W. -P.; De Hosson, J. Th. M. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical reasons the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Boelen et al, 2004 and performed peel-off experiments and found that the bonding between the polymer and steel is reduced by (pre) deformation of the steel substrate. Laser-induced delamination experiments by Fedorov et al, 2007 showed a similar result. Recent results from Faber et al, 2014 revealed the presence of interface damage in DRD materials by exploring the interface in cross-sections using Focused Ion Beam milling.…”
Section: Metal-polymer Laminatessupporting
confidence: 55%
“…Boelen et al, 2004 and performed peel-off experiments and found that the bonding between the polymer and steel is reduced by (pre) deformation of the steel substrate. Laser-induced delamination experiments by Fedorov et al, 2007 showed a similar result. Recent results from Faber et al, 2014 revealed the presence of interface damage in DRD materials by exploring the interface in cross-sections using Focused Ion Beam milling.…”
Section: Metal-polymer Laminatessupporting
confidence: 55%
“…The adhesion of organic coatings on aluminium is an important industrial topic for example in the packaging of food and beverages. The native oxide on aluminium is stable only in neutral environments (pH [4][5][6][7][8] where no chlorides are present. In the case of aluminium alloys precipitates form cathodic or anodic sites where localized corrosion can initiate.…”
Section: Introductionmentioning
confidence: 99%
“…It is known from literature that different parameters may result from different experiments (Vossen et al, 2014). An example of two experiments that result in a different work of separation (/) are the measurements of Fedorov et al (2007) and . The differences are explained by the distinct energy dissipated within the process zone, i.e.…”
Section: Interface Modelmentioning
confidence: 99%
“…The work of separation determined by Fedorov et al (2007) is used here. As the cohesive law used is different, the d n and d t parameters are estimated based on the results in Fedorov et al (2007). The resulting parameters used are listed in Table 2.…”
Section: Interface Modelmentioning
confidence: 99%